The role of positive atmosphere on learning generic skills in higher education—Experiences of physical education students - Virtanen, Anne; Lauritsalo, Kirsti; Mäkinen, Tommi; Hurskainen, Heikki; Tynjälä, Päivi (Frontiers in Education, 2022)
The purpose of this study is to examine what kind of role does positive atmosphere play in learning generic skills. The study was carried out in the final year of Finnish physical education (PE) teacher education where teachers of this study module have developed their pedagogical practices for a long time to foster and maintain the positive learning atmosphere of the course. In this study the learning atmosphere was examined from the perspectives of students addressing the following research questions: 1) How do the students perceive and experience the constructed learning atmosphere? 2) What generic skills do PE students learn during the final year study module? 3) What kind of relationship exists between the perceived learning atmosphere and learning generic skills? The data of this study were collected via internet questionnaire (N = 189, N = 123) and interviews (n = 19) and analysed applying qualitative content analysis and using statistical methods. According to the results, the PE students felt that the learning atmosphere of their final year study module was warm and conversational; it was easy to get their own voice heard during the final year. The PE students reported that they had learned versatile and plenty of different generic skills, particularly various social skills. There were statistically significant associations between positive atmosphere and some generic skills, such as the development of creativity, but they were not very strong. To understand this finding, the instruments of the study are discussed, especially from the perspective of the development of the questionnaire statements. Although the relationship between perceived positive atmosphere and learning generic skills was only moderate, the findings are promising. For example, the good practices documented in this study, such as how to construct a warm educational atmosphere, may be applied when developing other study modules.